To Whom Are Directors’ Duties Owed? Evidence from Canadian M&A Transactions - Hutchison, Camden (McGill Law Journal / Revue de droit de McGill, 2023)
One of the most contentious issues in corporate law is the proper scope of fiduciary duties. Many scholars have argued that fiduciary duties are owed exclusively to shareholders, while others have advocated a broader conception of directors’ fiduciary obligations, potentially encompassing a wide variety of stakeholder and community interests. This debate has both normative and positive dimensions: Not only are there theoretical disagreements as to whom directors’ duties should be owed, there are also more basic disagreements as to what the law actually requires, including the extent to which business norms supplement (or undermine) legal rules. In Canada, at least, jurisprudential and statutory reforms have broadened the scope of fiduciary duties to extend their protections to stakeholder groups including creditors, employees, and the environment.Or have they? In reality, there are reasons to believe that legal standards play a limited role in corporate governance, not least with respect to the fundamental question of in whose interests the corporation is to be governed. For public corporations, a variety of factors, including the professional norms of corporate managers, the realities of public financial markets, and the central role of shareholders in the mechanisms of corporate democracy, strongly encourage directors to prioritize shareholder interests. This article finds evidence of this phenomenon through an empirical study of “fiduciary out” provisions in Canadian M&A agreements. These provisions, which allow directors to abandon committed transactions in order to fulfill their fiduciary duties, are almost universally drafted in terms of maximizing shareholder value. Indeed, in two samples containing more than one thousand M&A agreements, only a single agreement permitted directors to consider non-shareholder interests. This evidence indicates that fiduciary duties are broader in theory than in practice.